Indigenous social work around the world : towards culturally relevant education and practice - Gray, Mel, 1951-; Coates, John, 1948-; Yellow Bird, Michael (Farnham, Surrey, England ; Burlington, VT : Ashgate, 2010)
This volume brings together prominent international scholars involved in both western and indigenous social work to discuss some of the most significant global trends and issues relating to indigenous and cross-cultural social work.
Includes bibliographical references and index.
Keywords: Social work with Indigenous peoples; Social work with Indigenous peoples -- Study and teaching; Society